A trianoni magyar-csehszlovák határmegállapítás egyik mozzanata : a politikai határbejárás 1921-1923 - Suba, János (Közép-Európai Közlemények, 2010)
In spring 1923 the leaders of the Hungarian and Czechoslovakian delegations made a joint tour of inspection to become acquainted with the local economic complaints of the separated territories. During this tour the demands and wishes of the interested parties have been recorded in order to be solved later by the two countries through bilateral contracts. The themes were as follow: existing and future water-privileges, rights of fishing, game laws, the maintenance and good repair of roads and bridges of mutual use, the permanent repair of the boundary marks, the direct communication of the administrative authorities of the border regions; the repair of certain road-sections and the wishes of the local people. The earliest possible arrangement of the borderland passenger and freight traffic meant essentials of life for the border-line landowners and for those working beyond the frontier but it became regulated only by Act XVII in 1927. Before this date there were only rules and ordinances of lower degree in operation.